Role of the Ilizarov External Ring Fixator in Gap Non-Union and Bone Loss Management - TUNIO, MUHAMMAD ZAIB; NOOR, FRAZ; ISHAQ, MUHAMMAD; QURESHI, ABDUL SAMAD; ABIDEEN, ZAIN-UL-; WAZIR AHMED, (Pakistan Journal of Medical & Health Sciences, 2025)
Background: Several surgical techniques are available to address segmental long-bone defects. Each technique has its own advantages and limitations. The Ilizarov bone plasty is a vital method for infected nonunion and compensating bone loss which has gained widespread popularity within the last few decades. Objective: To determine the role of the Ilizarov external ring fixator in gap non-union and bone loss management. Study Design: Observational study Place and Duration of Study: Department of Orthopaedics Unit-1, Chandka Medical College, SMBBU, Larkana from 1st October 2023 to 30th September 2024. Methodology: Sixty patients suffering from extensive tibial defects of more than ten centimetres were enrolled. The patients requiring bone gap union and bone loss management were included. Results: There were 43 males and 17 females with mean age 20.8±11.2. The mean bone defect value was 13.2±0.9 and anatomical shortening was 6.5± 0.8cm. The mean restoration of lower leg length was significantly higher as 88.8 ± 2.5%. The complications associated with the Ilizarov external ring fixator included highest presentation of skin inflammation up to 23.8% followed by recurrence of equinus in 18.3% and ankle stiffness presented in 11.6%. Conclusion: The Ilizarov external ring fixator has an efficient role in gap non-union and bone loss management.